40.2k views
3 votes
Suppose a-b=0. what equals a+b

User Hevski
by
7.1k points

2 Answers

2 votes

Answer:

a-b=0→ a=b

b=a

therefore it ends up being↓↓↓

a.b→→ substituting→→ a*(a)=a² or bxb=b²

hope this helps :)

↓↓↓edited ↓↓↓

<<<THIS IS WRONG I GUESS SO DONT LISTEN TO ME LOL>>>>

User Ataur Rahman Munna
by
7.3k points
5 votes

Answer:

2a or 2b

Explanation:

//No options to pick, but here it is:

a - b = 0 //Add b on both sides.

a = b

If a is equal to b then a = b can be written as a = a or b = b, if that true than:

a + b can be also written as:

a + a which makes its 2a or

b + b which is equal to 2b.

//Hope it helps.

User CppLearner
by
7.8k points